Associação de nanopartículas magnéticas a coagulantes orgânicos no tratamento de efluente de lavagem de materiais plásticos - Ribeiro, Thais (2019)
Nowadays industries and companies of diverse sectors see in the plastic an economic option of material with the purpose of to protect its products as well as to make them esthetic for the sector of sales. Given the high amount of plastic generated an alternative to not overburden landfills is the separation of waste for reuse or recycling. Thus, in order for the polymer to be properly recycled it is necessary to have the material cleaned, such work is carried out by plastic washing industries. For the treatment of the effluent from plastic washing, chemical coagulants such as Ferric Chloride or Aluminum Sulphate are usually used, however, due to the high concentration of solids present in the effluent in question, a large amount of sludge is generated having a large quantity of elements inorganic waste products such as iron and aluminum, thus needing to undergo a post treatment. Thus, the present study aims to test the efficiency of organic coagulants Moringa oleifera and Tanino in association with magnetic magnetite nanoparticle in order to accelerate the sedimentation process in the treatment of effluent from the washing of plastic materials in order to make them alternatives for use. The tests were carried out at the Universidade Tecnológica Federal do Paraná, Londrina campus. A pre-test was performed using the Jar-test methodology, which simulates the coagulation, flocculation and sedimentation processes of a treatment plant. The tests were performed in order to obtain the best concentration range of the coagulants in the presence and absence of the nanoparticle. This obtained strip was used to perform the initial part of the Central Rotational Composite Design (DCCR), so that the concentrations to be tested could be obtained as well as the times in which the behavioral analysis of the treatments were performed. The concentrations of Tannin used in the trial, defined by the DCCR analysis, were 13mgL-1, 14,45mgL-1, 18mgL-1, 21,55mgL-1 and 23mgL-1, while Moringa oleifera concentrations were 3mgL-1, 4.63mgL-1, 8mgL-1, 11.37mgL-1 and 13mgL-1. The concentration of nanoparticle used was 50mgL-1. During the test, the parameters pH, temperature, electrical conductivity, turbidity, apparent color, chemical oxygen demand and total solids were analyzed. After obtaining the data and statistical analysis (analysis of variance and response surface), it was observed that for the parameters of pH, temperature and electrical conductivity, the presence of the nanoparticle in the treatment was shown to be non-significant indicating, therefore, no influence on such parameters. As for the parameters of apparent Color and Turbidity the nanoparticle when associated with Moringa oleifera was not significant. However, the coagulant Tanino when associated to magnetite had its removal efficiencies high for both parameters, closing the test with maximum removals of 84% and 89% for apparent Color and Turbidity, respectively. For the removal of Total Solids all treatments obtained similar removals, being statistically non-significant between them. Regarding the COD parameter, the most prominent treatment was where the Tanino was associated to the nanoparticle, obtaining the highest removal 8 efficiency, which was 76% (Test 8). After analysis of all treatments, the best performance was related to the treatment using Tannin in association with magnetite at a concentration of 21.55mgL-1 and it was analyzed in the time of 28 minutes of sedimentation. Thus, it is concluded that organic coagulants associated with nanoparticles have the potential to become effluent treatment alternatives, thus replacing widely used inorganic coagulants.